Pengaruh Yoga Terhadap Kualitas Tidur Lansia (Elderly) - Sisilia Indriasari W; Ramadhan Andhika Putra (Poltekkes Kemenkes Surakarta, 2019)
Background: The aging process is followed by physiological changes that may affect the sleep quality of elderly. The phenomenon found in Posyandu Lansia (Elderly Health Center) of RW 03 Jagir sidomukti revealed the decrease of sleep quality in elderly such as insomnia, short period of sleep (5 hours per day), and difficulty in falling asleep after waking up. Methods: The purpose of this research was to analyze the influence of yoga on the sleep quality of elderly in Posyandu Lansia RW 03 Kelurahan Jagir Surabaya. This research applied pre-experimental one group pre-post test design. The sample of this research is elderly Posyandu Lansia RW 03 Jagir Surabaya that was taken using simple random sampling, with a total sample of 36 respondents. The independent variable of this research is yoga and the dependent variable is the sleep quality of elderly. The instrument applied in this research is PSQI for sleep quality. Results: Showed that 66.6% of the elderly had poor sleep quality before yoga and 77.7% had good sleep quality after yoga. The Wilcoxon rank test results obtained p = 0,000, with the value α = 0.05 where p <α H0 rejected. This indicates that yoga has an influence on the sleep quality of elderly. Based on the research result, it is suggested for the headman of RW 03 Kelurahan Jagir Surabaya and Puskesmas Jagir (Jagir Health Center) to hold yoga exercises regularly. Conclusion: It is also suggested for the health center to train their own yoga instructors so that they may instruct yoga for elderlies who cannot reach the health center in order to improve their sleep quality.